Citizenship education in building social capital for marine and coastal conservation - I Wayan Mudana (Jurnal Civics: Media Kajian Kewarganegaraan)
This study aimed to reveal the background of coastal communities in North Bali to develop texts on preserving coastal and marine resources. It also explored the various forms of social capital that are instrumental in the preservation of these resources, the process of dissemination of preservation texts, the social control mechanisms that maintain the stability of social capital and the preservation of beaches and seas, and the profound meaning of the social capital text it develops. This study used a qualitative approach. It revealed that coastal communities developed coastal and marine resource preservation texts driven by an awareness of the coast and sea as living spaces. The forms of social capital it develops are expressions, stories/myths, agreements, and social groups. The existence of social capital for coastal communities is not just a concept but a powerful force that functions in the preservation of coastal and marine resources. The text socialisation process involves family, dadia, banjar, organisations, and educational institutions. The mechanism of social control developed is from below and above, in an abstract sense, by involving various institutions. Developed social capital is meaningful for the harmonious relationship between humans and nature, humans with humans, humans with God, and the sustainability of the lives of coastal communities in North Bali.